Pengaruh Pemasaran Influencer Dan Citra Merek Terhadap Keputusan Pembelian Produk Scarlett Di Tiktok - Haris Sagala; Allen Kristiawan (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study aims to disseminate the influence of influencer marketing and brand image on purchase decisions for Scarlett products by active consumers on the TikTok social media platform. The quantitative approach used a causal explanatory design, explaining the causal relationship between variables and measuring the extent to which the independent variables, namely influencer marketing and brand image, influence the dependent variable, namely purchase decisions. The population in this study were consumers who had purchased Scarlett products through the TikTok platform. The sample was selected using a purposive sampling technique, with the criterion being individuals who had purchased Scarlett products at least once through TikTok. The resulting sample size was 157 respondents, which meets the minimum sample size guidelines based on the number of indicators. Data collection was conducted through a bold-print questionnaire using Google Forms, structured ordinally and focused on the variables studied. The test results showed that influencer marketing significantly influenced consumer purchase decisions. Similarly, brand image was shown to have a positive effect on purchase decisions for Scarlett products. Furthermore, both variables simultaneously had a significant effect on purchase decisions